(72^2/3)^1/2:36^1/6:2^1/3

(72^2/3)^1/2:36^1/6:2^1/3
Гость
Ответ(ы) на вопрос:
Гость
72 ^ ( 2/3 ) ^ 1/2 = ( 36 ^ 2/3 ) ^ ( 1/2 ) * ( 2 ^ 2/3 ) ^ ( 1/2 ) =  = ( 36 ^ 1/3 ) * ( 2 ^ 1/3 )  ----------------------------------- ( 36 ^ 1/3 ) * ( 2 ^ 1/3 ) : ( 36 ^ 1/6 ) = 36 ^ ( 1/6 ) * 2 ^ ( 1/3 )  ---------------------------------------- 36 ^ ( 1/6 ) * 2 ^ ( 1/3 ) : 2 ^ ( 1/3 ) = 36 ^ ( 1/6 )  ----------------------------------------- ОТВЕТ 36 ^ ( 1/6 ) 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы